2003
DOI: 10.1002/jlcr.795
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of fluorine‐18‐labelled fluoromisonidazole using two different synthesis methods

Abstract: The second method (II) was the fluorination of the protected precursor 1-(2 0 -nitro-1 0 -imidazolyl)-2-O-tetrahydropyranyl-3-O-toluenesulphonyl-propanediol, followed by a rapid removal of the protecting group. With the first method, the radiochemical yield was about 10% at the end of the synthesis (EOS), and the radiochemical purity was over 99%. The radiochemical yield in the second method was 21% (EOS) on an average, and the radiochemical purity was over 97%. When an automated commercial synthesis module wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 9 publications
(5 reference statements)
1
22
0
Order By: Relevance
“…(Kämäräinen et al, 2004) We believe the higher specific activity of [ 18 F] FMISO reported using this microfluidics synthesizer compared with macroreactors is in part due to the reduced surface area of the fluorinated polymers the [ 18 F] fluoride solution is in contact with during the synthesis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…(Kämäräinen et al, 2004) We believe the higher specific activity of [ 18 F] FMISO reported using this microfluidics synthesizer compared with macroreactors is in part due to the reduced surface area of the fluorinated polymers the [ 18 F] fluoride solution is in contact with during the synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…Our yields for the synthesis of an average radiochemical yield of 58% are equal to that previously reported in the literature. (Kämäräinen et al, 2004; Tang et al, 2005) An advantage of our system is that unlike current commercially available macroscale radiochemistry systems, either cassette or reactor based, our system allows for multiple runs per day without requiring entry into the hot cell containing the high radiation field.…”
Section: Discussionmentioning
confidence: 99%
“…However, FMISO exhibits some disadvantages, such as the slow clearance kinetics resulting in delaying specific imaging for 2-3 hr postinjection, and Methods high lipophilicity of FMISO resulting in substantially high background, which can interfere with the image's quality. FMISO is currently being used as an in vivo marker to noninvasively assess hypoxia in human malignancies and in the hearts of patients with myocardial ischemia with PET imaging (Graham et al, 1997;Kamarainen et al, 2004), and plays an important role in predicting the oxygenation status in tumors during radiotherapy. Although these potential PET tracers can overcome some limitations of FMISO, FMISO still is now the most widely used radiotracer in clinical PET imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic strategies of FMISO can be divided into two main groups: (1) a nucleophilic substitution on a protected precursor with subsequent removal of the protection group (Kamarainen et al, 2004;Lim and Berridge, 1993;Pattet al, 1999) or epoxide ring-opening (Jerabek et al, 1986); and (2) the production of a 18F-labeled intermediate epifluorohydrin with subsequent coupling to the nitroimidazole moiety under basic conditions (Kamarainen et al, 2004). Both approaches have their limitations.…”
Section: Introductionmentioning
confidence: 99%
“…8 Among the different methodologies described to obtain this derivative, it can be highlighted the synthesis through fluoride displacement of a primary tosylated alcohol, and subsequent deprotection of the tetrahydropyranyl protecting group from the secondary alcohol under acidic conditions (Scheme 1A). 9 Very recently it has been proposed the first asymmetric synthesis of (S)-1 via enantioselective aperture of an epoxide precursor with 1,1,1,3,3,3-hexafluoroisopropanol (HFIP), 5-diazabicyclo[4.3.0]non-5-ene (DBN), benzoyl fluoride, and a linked (salen)Co catalyst to achieve the kinetic resolution obtaining it in 93% ee and 40% yield (Scheme 1B). Due to the short half-life of 18 F-labeled F-MISO, it would be highly desirable to find a methodology that could easily afford both stable unlabeled F-MISO antipodes so the different biological properties of each enantiomer could be more easily assessed.…”
mentioning
confidence: 99%